2016
DOI: 10.1162/jocn_a_00887
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Processing of Numerical and Nonnumerical Magnitudes in the Brain: An fMRI Study

Abstract: It is well established that, when comparing nonsymbolic magnitudes (e.g., dot arrays), adults can use both numerical (i.e., the number of items) and nonnumerical (density, total surface areas, etc.) magnitudes. It is less clear which of these magnitudes is more salient or processed more automatically. In this fMRI study, we used a nonsymbolic comparison task to ask if different brain areas are responsible for the automatic processing of numerical and nonnumerical magnitudes, when participants were instructed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 43 publications
(48 reference statements)
4
33
1
Order By: Relevance
“…Areas of the ventrolateral prefrontal cortex, medial anterior cortex, and right IPS demonstrated task‐positive ratio effects, similar to meta‐analyses of number processing tasks (Sokolowski et al, ), indicating their functional role in numerical magnitude perception. Results for incongruent > congruent trials are similar to the only two previous studies to execute a comparable contrast with the nonsymbolic number comparison task (Leibovich, Vogel, Henik, & Ansari, ; Wilkey et al, ) in that all three showed significantly greater activity during incongruent trials in the rIFG and Wilkey et al () also showed similar effects in the fusiform gyrus, although those previous studies involved adults and adolescents, respectively. A large body of work supports the notion that a right‐lateralized portion of the inferior frontal cortex is critical for inhibiting response tendencies more generally and orienting to behaviorally relevant stimuli (reviewed in Aron & Poldrack, ; Aron, Robbins, & Poldrack, ; for meta‐analysis see Levy & Wagner, ).…”
Section: Discussionsupporting
confidence: 85%
“…Areas of the ventrolateral prefrontal cortex, medial anterior cortex, and right IPS demonstrated task‐positive ratio effects, similar to meta‐analyses of number processing tasks (Sokolowski et al, ), indicating their functional role in numerical magnitude perception. Results for incongruent > congruent trials are similar to the only two previous studies to execute a comparable contrast with the nonsymbolic number comparison task (Leibovich, Vogel, Henik, & Ansari, ; Wilkey et al, ) in that all three showed significantly greater activity during incongruent trials in the rIFG and Wilkey et al () also showed similar effects in the fusiform gyrus, although those previous studies involved adults and adolescents, respectively. A large body of work supports the notion that a right‐lateralized portion of the inferior frontal cortex is critical for inhibiting response tendencies more generally and orienting to behaviorally relevant stimuli (reviewed in Aron & Poldrack, ; Aron, Robbins, & Poldrack, ; for meta‐analysis see Levy & Wagner, ).…”
Section: Discussionsupporting
confidence: 85%
“…In contrast to the IPS, the IFG was the brain region most consistently modulated by the congruency between numerical and nonnumerical variables during the comparison tasks. Incongruent trials consistently elicited a greater response in this region, a finding that was present in all four studies (three in the right IFG and one in the left IFG). And, in children, individual differences in this congruency effect during number comparison right IFG correlated with mathematics achievement, with a smaller congruency effect relating to better math achievement (Fig.…”
Section: Challenge 3: Measures Of Number Sense Are Not Measuring Numbsupporting
confidence: 62%
“…Previous neuroimaging research has shown that congruent and incongruent trials of the nonsymbolic number comparison task recruit different neural mechanisms, with incongruent trials recruiting large portions of the frontoparietal attention network (Leibovich, Vogel, Henik, & Ansari, ; Wilkey, Barone, Mazzocco, Vogel, & Price, ). Recruitment of additional neurocognitive mechanisms during incongruent trials may be an integral component of the previously assumed direct relation between ANS and mathematics achievement in studies of mathematics learning disability, but also across the full range of achievement.…”
Section: Discussionmentioning
confidence: 99%